The Pro-Decentralization Effect on Management of Local Enterprises: A Structural Model of the Case of Bamenda III municipality Mezam Division, Cameroon - Ofeh, Moses Abit; Thalut, Nashipu (Archives of Business Research, 2021)
The study was aimed at investigating the effect of pro-decentralization on management of local enterprises in Bamenda III municipality, North West Region of Cameroon. Data was derived through the use of questionnaire on a sample of 500 registered voters and businessmen who have knowledge of local enterprises in Bamenda III using purposive sampling approach. The objective was achieved by applying maximum likelihood estimation technique of structural equation modelling using SmartPLS software version 2. The empirical results revealed that pro-decentralization has a significant positive effect on the management of local enterprises and corruption orientation. Corruption orientation has a negative influence on the management of local enterprises, though not found to be significant. The finding indicated that a unit increase in pro-decentralization has the tendency to improve the management of local enterprises to the tune of 63%. The study therefore recommends that policies of decentralization should be corruption free and should be directed towards enhancing service quality of local enterprises.